(untitled) (Al-Academy, 2024)
The study aims to reveal the formal approaches in the sculptural monuments of the Arabian Peninsula, along with their formal approaches in the arts of the modern era in terms of similarities and differences between the two styles and the contrast in intellectual references, and in the structure of the image system, in addition to discovering the underlying relationships between shapes and the combination of elements and their symbolic meanings. The research consists of Several chapters. The first chapter included the theoretical framework and included two axes: the formal approach between ancient sculptural monuments and modern sculpture, and the formal approach between ancient monumental sculptures and contemporary Arab sculpture. The second chapter consists of analyzing the sample samples, while the third chapter consists of the research results, there is a noticeable convergence with the sculptural monuments of the Arabian Peninsula, and in both styles the convergence appears in reductionism, simplification, symbolism, and structural elements, in terms of combining movement, stasis, balance, ambiguity, and the imaginative dimension.